Gestión de cuentas por cobrar y su incidencia en la liquidez de las empresas comercializadoras de agroquímicos en el distrito de Trujillo. - Loyola Ibañez, Christian Stevenson (2016)
This research develops around the assessment of the impact of the management of accounts receivable in the liquidity of the trading companies of agrochemicals in the district of Trujillo , based on the analysis of financial statements and applying the relevant ratios which together to analyze the degree of liquidity of these businesses . The main objective was to establish how short-term management of accounts receivable a positive impact on the liquidity of the trading companies of agrochemicals in the district of Trujillo in such a way as to achieve solid results to make decisions about the fulfillment of obligations. The universe consisted of all agrochemical companies trading district of Trujillo and the sample was determined Agropecuaria Chimú S.R.L. Through the investigation I have obtained results which show that the management of accounts receivable significantly affects the generation of liquidity for trading agrochemical companies.